Developing Academic Thinking in the EFL Writing Classroom: A Rationale for General-academic Writing Assignments - Zalewski, Jan (Complutense Journal of English Studies, 2020)
With the evidence for disciplinary variation in academic discourse constantly growing, the idea of teaching core academic thinking in writing seems to have become increasingly problematic. The paper offers a rationale for two general-academic writing assignments, each focusing on teaching one fundamental aspect of what is defined as the intellectual stance underlying academic writing in general. The two aspects are problematizing and subject position. Problematizing and assuming a new subject position in the context of academic writing prove to be troublesome tasks for many entering college students. The assignments are designed to help students cope with these problems. They are based on a reactive approach rather than on modelling academic discourse, with the teacher helping students to reflect on their rendering of familiar experiences.